Development of Leadership Competency Framework for Board of Management Members in Private Enterprises Using a Delphi Method - Hải, Hồ Như; Anh, Đỗ Vũ Phương (VNU Journal of Science: Policy and Management Studies, 2016)
Abstract : There are many methods to develop leadership competency framework but none can be consider perfect as there are pros and consto of each method. The purpose of this paper is to present the use ofDelphi method to develop leadership competency framework for members of the board of management in private enterprises. TheDelphi method is a qualitative research approach used to obtain a consensus of opinion of the group of experts using questionnaires. TheDelphi research was conducted based on the initial list of 27 leadership competencies collected from multinational corporations. After the third round of the Delphi research, the developed competency frameworks for chief executive officer, chief people officer, chief customer officer, chief financial officer, chief marketing officer and chief information officer using theDelphi method are valid and reliable. Each competency framework contains the 12 most important competencies to the board of management member out of the initial list of 27 leadership competencies.  Keywords: leadership competency framework, members of the board of management, private enterprises, Delphi method.